2014
DOI: 10.1104/pp.114.237602
|View full text |Cite|
|
Sign up to set email alerts
|

A Limited Role for Carbonic Anhydrase in C4 Photosynthesis as Revealed by a ca1ca2 Double Mutant in Maize    

Abstract: Carbonic anhydrase (CA) catalyzes the first biochemical step of the carbon-concentrating mechanism of C4 plants, and in C4 monocots it has been suggested that CA activity is near limiting for photosynthesis. Here, we test this hypothesis through the characterization of transposon-induced mutant alleles of Ca1 and Ca2 in maize (Zea mays). These two isoforms account for more than 85% of the CA transcript pool. A significant change in isotopic discrimination is observed in mutant plants, which have as little as 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
97
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 51 publications
9
97
2
1
Order By: Relevance
“…Many of the proteins thought to be involved in C 4 photosynthesis are members of such paralogous groups (Taniguchi et al, 2004;Rondeau et al, 2005;Shenton et al, 2006;Studer et al, 2014). Although this redundancy likely enables the evolution of new activities, it also makes it difficult to determine which of the genes have been co-opted to participate in C 4 photosynthesis (Bräutigam et al, 2008;Majeran and van Wijk, 2009;Weber and von Caemmerer, 2010).…”
Section: Dct2 Is a Primary Transporter For Malate Into The Bs Chloropmentioning
confidence: 99%
“…Many of the proteins thought to be involved in C 4 photosynthesis are members of such paralogous groups (Taniguchi et al, 2004;Rondeau et al, 2005;Shenton et al, 2006;Studer et al, 2014). Although this redundancy likely enables the evolution of new activities, it also makes it difficult to determine which of the genes have been co-opted to participate in C 4 photosynthesis (Bräutigam et al, 2008;Majeran and van Wijk, 2009;Weber and von Caemmerer, 2010).…”
Section: Dct2 Is a Primary Transporter For Malate Into The Bs Chloropmentioning
confidence: 99%
“…CA antisense constructs, which reduce the activity of cytosolic CA in Flaveria bidentis mesophyll cells by at least 70%, lead to diminished rates of photosynthesis, although CA levels must be severely reduced in order to see effects on photosynthesis rates, due to the high enzymatic activity of CA (von Caemmerer et al, 2004). In maize (Zea mays), insertional mutants of the ca1 and ca2 genes decreased plant growth but led to no significant changes in photosynthesis rates, suggesting possible anapleurotic roles for CA (Studer et al, 2014).…”
mentioning
confidence: 99%
“…It has been suggested that CA activity in C4 plants is near rate limiting for photosynthesis (Hatch and Burnell, 1990;Cousins et al, 2008). A recent study in maize (Zea mays) showed that CAs are not limiting for C4 photosynthesis, at least at current ambient CO 2 conditions, but become limiting at low CO 2 concentrations in leaves (partial pressure of CO 2 inside leaf [C i ]; Studer et al, 2014). Photosynthetic rates in maize ca1ca2 double-mutant plants were not reduced under current and elevated CO 2 partial pressures but were impaired at low partial pressures (Studer et al, 2014).…”
mentioning
confidence: 99%
“…A recent study in maize (Zea mays) showed that CAs are not limiting for C4 photosynthesis, at least at current ambient CO 2 conditions, but become limiting at low CO 2 concentrations in leaves (partial pressure of CO 2 inside leaf [C i ]; Studer et al, 2014). Photosynthetic rates in maize ca1ca2 double-mutant plants were not reduced under current and elevated CO 2 partial pressures but were impaired at low partial pressures (Studer et al, 2014). In C3 plants, the roles of CAs in limiting photosynthesis are less clear, but gCAs do have biological roles in mitochondrial physiology (Perales et al, 2005) and function in male sterility (Villarreal et al, 2009).…”
mentioning
confidence: 99%